Iconic violence: belief, law and the visual. Issue 1 (2nd January 2018) - Kayman, Martin A.
ABSTRACT: In early 2015, the attacks provoked by cartoons of the Prophet and the execution videos released by Islamic State staged a bloody encounter between two aesthetics of the image and two visions of its law. The confrontation between caricature and documentary realism and between blasphemy and freedom of expression form the context for this inquiry into the violence associated with beliefs about images. Violence can arise not only as a result of religious beliefs but equally from the contribution of visual evidence to secular convictions. The article shows how recent reassessments of the ethics of 'law and the visual' draw on the emancipatory discourses of the 'pictorial turn' and its recourse to the discourse of the early iconoclastic debates. The key legacy of the Byzantine debates, I argue, is less a theory of the image as the polemical identification of the iconoclast and the idolater and the management of the violent passions they evoke for each other. What is ultimately at issue in laws governing relations between seeing and believing are the attitudes people have to those who do not share their regime of the visual, and which, at times of crisis, can revive passions associated with veneration and execration.